Strategi Resiliensi Bisnis Mice Melewati Era Pandemi Menuju Endemi - Sinaga, Lia Agustin; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i01.p18, 2024)
Entering the endemic era, the MICE business looks to be getting better. Even so, during the COVID-19 pandemic, MICE industry was one of the industries affected. Business resilience is needed to survive this crisis. This study aims to determine the condition of PT. Jaya Impian Abadi amid a pandemic and how resilience and adaptation strategies were carried out in passing the pandemic and now entering the endemic era. This study uses the case study method with a qualitative approach. Collection using in-depth interviews with the director of PT. Jaya Impian Abadi and literature studies. The results of this study indicate that the resilience strategy of PT. Jaya Impian Abadi in dealing with a pandemic begins with overcoming problems by imposing work from home as a form of survival amidst a pandemic, starting to switch businesses to become a supplier of health tools and products as well as merchandise, following trends and utilizing technology in online and hybrid events, and maintaining good relationships with clients during the pandemic so that in the endemic era, PT. Jaya Impian Abadi can reach the target again. Keywords: MICE, Recilience, Pandemic, Endemic, Strategic